2006
DOI: 10.1063/1.2358827
|View full text |Cite
|
Sign up to set email alerts
|

Improved dielectric properties of bismuth-doped LaAlO3

Abstract: Articles you may be interested inEffect of Pr-and Nd-doping on structural, dielectric, and magnetic properties of multiferroic Bi0.8La0.2Fe0.9Mn0.1O3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This phase transition is pressure dependent and is accompanied by the rotations of the adjacent AlO 6 octahedral about the [111] direction and relative compression of the LaO 12 polyhedron [16]. LaAlO 3 has been pointed as promising for substitute SiO 2 as high-K gate dielectric due to its many advantages, such as good dielectric properties with high relative permittivity and low-temperature dependence of the resonant frequency [17]. This compound is widely used as substrate for growing thin films and it is a promising material to prepare substrates for the development of the high-speed devices [18].…”
Section: Introductionmentioning
confidence: 99%
“…This phase transition is pressure dependent and is accompanied by the rotations of the adjacent AlO 6 octahedral about the [111] direction and relative compression of the LaO 12 polyhedron [16]. LaAlO 3 has been pointed as promising for substitute SiO 2 as high-K gate dielectric due to its many advantages, such as good dielectric properties with high relative permittivity and low-temperature dependence of the resonant frequency [17]. This compound is widely used as substrate for growing thin films and it is a promising material to prepare substrates for the development of the high-speed devices [18].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, these compounds exhibit ferroelectricity, pyroelectricity, ferromagnetism, superconductivity, colossal magnetoresistance, catalytic properties etc. [1][2][3][4][5][6][7][8], which render them as some of the most important technical materials. The perovskite LaCoO 3 system is a promising thermoelectric material due to its high Seebeck coefficient of 600 mV/K at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…7 shows the frequency dependences of the room-temperature dielectric constant and dielectric loss of the LBAO specimens derived from two-step molten method. The patterns of dielectric properties show the larger frequency dispersion phenomena compared to the reported data by Zylberberg and Ye [8], revealing the strong relaxor nature of LBAO ceramics densified from nanostructures. The dielectric constant measured at 50 Hz is 37.5, which is already higher than the literature values of 22-27 [15,16] estimated from the capacitance-voltage (C-V) curves of the paraelectric LaAlO 3 material.…”
Section: Resultsmentioning
confidence: 61%
“…In the lead-free oxides, lanthanum aluminate, LaAlO 3 , has received tremendous interest because it has a large band gap energy of 5.6 eV, a relatively high dielectric constant of 20-27, and is thermally stable up to 2100°C [4][5][6][7]. Recently, Ye et al have found that the introduction of bismuth ions to LaAlO 3 favors to improve the dielectric properties, which can be attributed to the high polarizability of Bi 3+ ion with a lone electron pair [8]. Later, Si et al synthesized a LaAlO 3 -BiAlO 3 ceramic system through the conventional solid-state reaction and reported that La 0.9 Bi 0.1 AlO 3 (LBAO) composition enjoys excellent dielectric relaxor properties compared to pure LaAlO 3 paraelectric ceramics [9].…”
Section: Introductionmentioning
confidence: 98%